Internalization Arabic Language Skills In Improving Understanding Islamic Religious Studies Students of Islamic Religious Education STAI As-Sunnah Deli Serdang - Saifundi; Salminawati; Zaini Dahlan (Journal of Educational Sciences, 2025)
This study discusses the internalization of Arabic language skills to enhance the understanding of Islamic religious knowledge among students of the Islamic Religious Education Study Program at STAI As-Sunnah Deli Serdang. Arabic plays a crucial role in understanding key Islamic sources, such as the Qur'an and Hadith. The research adopts a qualitative approach using techniques such as observation, interviews, and documentation. The results reveal that students' Arabic language skills vary, but the majority are capable of understanding Arabic texts. The integrative learning strategies employed have proven effective in linking linguistic abilities with a deeper understanding of Islam. Supportive factors include a competent academic environment and skilled lecturers, while challenges include a lack of variation in teaching methods and limited opportunities for language practice. Therefore, more effective strategies are needed, such as a bilingual curriculum, intensive training, and interactive learning media, to further enhance students' understanding of Islamic religious knowledge in a more profound way.